Cytogenetic and molecular aberrations and worse outcome for male patients in systemic mastocytosis - Kluin-Nelemans, Hanneke C; Jawhar, Mohamad; Reiter, Andreas; van Anrooij, Bjorn; Gotlib, Jason; Hartmann, Karin; Illerhaus, Anja; Oude Elberink, Hanneke N G; Gorska, Aleksandra; Niedoszytko, Marek; Lange, Magdalena; Scaffidi, Luigi; et al. (Theranostics, 2021)
In systemic mastocytosis (SM), the clinical features and survival vary greatly. Patient-related factors determining the outcome in SM are largely unknown. Methods: We examined the impact of sex on the clinical features, progression-free survival (PFS), and overall survival (OS) in 3403 patients with mastocytosis collected in the registry of the European Competence Network on Mastocytosis (ECNM). The impact of cytogenetic and molecular genetic aberrations on sex differences was analyzed in a subset of patients. Results: Of all patients enrolled, 55.3% were females. However, a male predominance was found in a subset of advanced SM (AdvSM) patients, namely SM with an associated hematologic neoplasm (SM-AHN, 70%; p < 0.001). Correspondingly, organomegaly (male: 23% vs. female: 13%, p = 0.007) was more, whereas skin involvement (male: 71% vs. female: 86%, p = 0.001) was less frequent in males. In all patients together, OS (p < 0.0001) was significantly inferior in males, and also within the WHO sub-categories indolent SM, aggressive SM (ASM) and SM-AHN. PFS was significantly (p = 0.0002) worse in males when all patients were grouped together; due to low numbers of events, this significance persisted only in the subcategory smoldering SM. Finally, prognostically relevant cytogenetic abnormalities (10% vs. 5%, p = 0.006) or molecular aberrations (SRSF2/ASXL1/RUNX1 profile; 63% vs. 40%, p = 0.003) were more frequently present in males. Conclusions: Male sex has a major impact on clinical features, disease progression, and survival in mastocytosis. Male patients have an inferior survival, which seems related to the fact that they more frequently develop a multi-mutated AdvSM associated with a high-risk molecular background.
Keywords: Leukemia, Myeloid, Acute; novorozenec; Infant, Newborn; Sex Factors; splenomegalie; Infant; Humans; Hematologic Neoplasms; Proto-Oncogene Proteins c-kit; kojenec; lidé středního věku; Skin Diseases; dítě; protoonkogenní proteiny c-kit; Child; Female; Aged; mladý dospělý; dospělí; Mastocytosis, Systemic; Leukemia, Mast-Cell; senioři; lidé; mastocytární leukemie; gastrointestinální nemoci; systémová mastocytóza; Mastocytosis; sex difference; represorové proteiny; doba přežití bez progrese choroby; Splenomegaly; hepatomegalie; Hepatomegaly; hematologické nádory; myelodysplastické syndromy; sexuální faktory; survival; předškolní dítě; Adult; serin-arginin sestřihové faktory; kožní nemoci; chromozomální aberace; ženské pohlaví; Core Binding Factor Alpha 2 Subunit; Repressor Proteins; Chromosome Aberrations; Male; Middle Aged; Serine-Arginine Splicing Factors; Adolescent; prognóza; cytogenetics; Aged, 80 and over; Young Adult; molecular mutations; senioři nad 80 let; Progression-Free Survival; Myelodysplastic Syndromes; protein PEBP2A2; míra přežití; mužské pohlaví; Child, Preschool; Gastrointestinal Diseases; akutní myeloidní leukemie; Prognosis; mladiství; Survival Rate